2012
DOI: 10.1002/jpln.201100209
|View full text |Cite
|
Sign up to set email alerts
|

Responses of barley to hypoxia and salinity during seed germination, nutrient uptake, and early plant growth in solution culture

Abstract: The resistance of most plants to salt can be impaired by concurrent waterlogging. However, few studies have examined this interaction during germination and early seedling growth and its implications for nutrient uptake. The aim of the study was to examine the response of germination, early growth, and nutrient uptake to salt (NaCl) and hypoxia applied to barley (Hordeum vulgare L. cv. Stirling), in solution culture. Hypoxia, induced by covering seeds with water, lowered the germination from 94% to 28% but sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…The absorption of nutrients by plants is inhibited by salt–alkali stress 46 , 47 , and the lack of a particular nutrient element changes the metabolism of plants and affects the biosynthesis of metabolites. Salt stress is primarily caused by excess salt ions in soil, and rebuilding ion homeostasis under salt–alkali stress remains an important salt-tolerance strategy in plant cells 13 , 48 .…”
Section: Discussionmentioning
confidence: 99%
“…The absorption of nutrients by plants is inhibited by salt–alkali stress 46 , 47 , and the lack of a particular nutrient element changes the metabolism of plants and affects the biosynthesis of metabolites. Salt stress is primarily caused by excess salt ions in soil, and rebuilding ion homeostasis under salt–alkali stress remains an important salt-tolerance strategy in plant cells 13 , 48 .…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the Na/K ratios in the leaves and stems were higher than that in the roots, which is similar in Tibetan wild barley under salt stress [62], indicating that maintaining an optimal Na/K ratio could improve salt tolerance. Kirmizi and Bell [71] reported that nutrient element uptake and distribution in plant tissues are affected by salt stress. In this study, we also found that Ca, Cu, Fe, Mg, and K contents decreased in roots, stems and leaves under salt stress.…”
Section: Discussionmentioning
confidence: 99%
“…The negative effect of the T6 water on seed germination of Cicer may be attributed to the high TDS, conductivity and chloride content. There are reports that suggests seed germination is negatively affected by salinity through osmotic effects (Zhang et al 2010;Krmz & Bell 2012), by ion toxicity (Hampson & Simpson 1990) or by a combination of the two (Huang & Redmann 1995).…”
Section: Resultsmentioning
confidence: 99%